¿El proyecto de movilidad “Quito Cables”Conflicto o solución? - Narváez Carrión, Jessica Fernanda (2018)
The present academic essay is a compendium of the process of metropolitan transformation of Quito, the currents of globalization and the model of urban expansion provoked new forms of territorial structures that are marked by a strong fragmentation and socio-territorial segregation; characterized by access to the ground. The implementation of land transport competition to understand the current mobility situation of the city, the challenges and challenges that the Municipality must face. The main purpose is to analyze and understand the cultural political effects caused by the mobility proposal "Quito Cables", in the barrios of the Northwest of Quito, under the slogan of solving the mobility problems in these sectors with an innovative initiative, this under the analysis of discourses, perceptions of the actors themselves and the review of documents that support the project. A descriptive analysis of the hand of authors like Harvey, Borja, Sabatini has been carried out to interpret the socio-cultural reaction of the urban sectors affected by the municipal proposal within the framework of the right to the city, for which three sections have been established in the which is analyzed: i) the Quito metropolitan process, competition in transport and the right to the city, ii) the "Quito Cables" mobility project and the segregative context of the northwestern neighborhoods and, finally; iii) The conflict and the different actors that emerge from the municipal proposal, with the closing of the main conclusions regarding whether the approach of this project contributed to the solution or conflict for the local government.